Use of triazoles for the treatment of invasive aspergillosis: A three‐year cohort analysis. Issue 1 (30th October 2019) - Cheng, Matthew P.; Orejas, José L.; Arbona‐Haddad, Esther; Bold, Tyler D.; Solomon, Isaac H.; Chen, Kaiwen; Pandit, Alisha; Kusztos, Amanda E.; Cummins, Kaelyn C.; Liakos, Alexis; Marty, Francisco M.; Koo, Sophia; et al.
Summary: In a 3‐year cohort study of adult patients with proven or probable IA, fewer patients initially treated with isavuconazole experienced adverse events compared with voriconazole, but more patients required a change in therapy due to lack of clinical efficacy.